Model of turbulence and results of calculations of flat turbulent near-wall flows - Мамчук, В. І. (Proceedings of National Aviation University (archive), 1998)
Presented is mathematical model of turbulence and results of calculations of near-wall flows according to proposed "final-result" method. Calculated parameters of some flows are compared with known experimental datas